Elfa monitoring systems: um sistema de monitoramento de pessoas idosas por meio de sensores, utilizando internet das coisas - Carvalho, Maria Luzia Silva de (Universidade Federal Rural do Semi-Árido, 2019)
There is a great growth in the proportion of aged people in the world, and one of their main necessities is having an independent lifestyle. However, in the old age, people tend to be more liable to accicents, such as falls, burns, electric shoks, or even forgetting to do certain chores as taking medicine, turning o electronic equipment after using them, turning o taps, among others. Many researches are being done aiming the development of a system for monitoring the activities of an aged person who lives with relatives or by itself, so that help can be given before the situation becomes severer. In this context, the objective of this work is the dvelopment of a system for monitoring and acknowlegeing falls of and aged people in both internal and external environments, called Elfa Monitoring Systems, making use of an electronic circuit with integrated accelerometer and using Internet of Things in order to recieve and transmit alert signals to relatives and/or doctors.
Keywords: Idosos; Internet das Coisas; Monitoramento; Queda; Sensores; Old People; Internet of Things; Monitoring; Fall; Sensors; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO